2011
DOI: 10.5336/medsci.2010-19917
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Affective Temperament in Knee Osteoarthritis Patients and Its Effects on Physical Therapy Response

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: : To de ter mi ne the most com mon do mi nant af fec ti ve tem pe ra ment and its ef fects on the physi cal the rapy out co mes in pa ti ents with kne e os te o art hri tis (OA). M Ma a t te e r ri i a al l a an nd d M Me et t h ho od ds s: : One hun dred and fi ve pri mary kne e OA pa ti ents re fer red with kne e pa in we re as sessed for eli gi bi lity. Eighty-six pa ti ents who met inc lu si on and exc lu si on cri te ri a we re inc lu ded in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Thus, if there are no differences, either between groups with OA, or groups with CS, but there are differences between FM and OA-noCS, we could assume that the HA dimension is the key. In Çidem et al's [23] knee OA research where they studied the personality profile, they found that the depressive temperament was the most frequent for these patients. This temperament has common features with the HA dimension, for example, being worried, passive, pessimistic, and anxious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if there are no differences, either between groups with OA, or groups with CS, but there are differences between FM and OA-noCS, we could assume that the HA dimension is the key. In Çidem et al's [23] knee OA research where they studied the personality profile, they found that the depressive temperament was the most frequent for these patients. This temperament has common features with the HA dimension, for example, being worried, passive, pessimistic, and anxious.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known in the field of personality in OA, although it is the most prevalent musculoskeletal disease; presumably, plenty of OA patients suffer CP, and there are studies that show that the patient's personality predicts recovery after total knee arthroplasty [22]. Çidem, Rezvani, and Karacan [23] studied personality in patients with knee OA, defined as affective temperament (depressive, hyperthymic, cyclothymic, irritable, and anxious), which describes the attitudes and behavior of individuals based on the constitutional, genetic, and biological factors. In knee OA patients, depressive temperament (hypercritical or complaining, passive or indecisive, self-critical, pessimistic, incapable of fun, and becoming worried) was the most common dominant affective temperament.…”
Section: Introductionmentioning
confidence: 99%